TAZKIYATUN NAFS-BASED ART THERAPY IN GENERATION Z'S EMOTION REGULATION: : A CASE STUDY AT MTSN 6 SUMEDANG - Oktaviani, Eka Chandra (Universitas Islam Negeri Mataram, 2025)
Generation Z faces various emotional challenges due to high digital exposure and rapid social change. Emotion regulation is an important aspect of their psychological well-being. Art therapy has been proven as an effective method in helping individuals express and manage emotions in a healthy manner. On the other hand, the concept of tazkiyatun nafs in Islam emphasizes purification of the soul as part of mental and spiritual strengthening. Therefore, this study aims to analyze the effectiveness of tazkiyatun nafs-based art therapy in helping Gen-Z regulate their emotions at MTSN 6 Sumedang. This study used a phenomenological qualitative approach with participants as many as 10 students who experienced difficulties in emotion regulation. Data were collected through in-depth interviews before and after the intervention, as well as observation during art therapy sessions combined with tazkiyatun nafs values. Data analysis was conducted using thematic analysis techniques. The results showed that this approach helped participants to increase emotional awareness, manage stress, and strengthen their spiritual dimension. Participants who initially experienced difficulties in expressing feelings began to show improvement in understanding and controlling emotions more positively. The integration of Islamic values in art therapy also had a significant impact in building their psychological balance. Tazki-based art therapy